Le commerce mozabite - Kleinknecht, Charles (Centre des hautes études sur l'Afrique et l'Asie moderne, 1962)
Keywords: Commerce -- Mzab

Taxation des corporations professionnelles d’Alger à l’époque turque - Hoexter, Miriam (Revue de l'Occident musulman et de la Méditerranée, 1983)
The permanent Muslim population of Algiers and the Jewish community, as well as the Barrāniyya (people from outside the city) are mentioned. The Barrāniyya were organized in six corporations: people from Mīzāb, Biskra, Djidjilī, Laghouat, the tribe of Mzīṭa, and the liberated blacks. Sources for this study have been: books of travellers and foreign consuls residing in Algiers in the period in question (end 17th century-1830), registers of the Turkish government of Algiers, including the Tachrifāt, and documents and official publications of the first years of the French occupation.
Keywords: Commerce -- Mzab

Le comportement économique des musulmans. Une exception: les Mozabites - Chabert, Alexandre (Revue d’Histoire Économique et Sociale, 1961)
A survey of Mīzābī commercial activity in Mīzāb and, especially, outside Mīzāb, with official statistical data
Keywords: Commerce -- Mzab

Les marchés du Mzab - Gandolfi, Alain (Ecole Nationale de la France d'Outre-Mer, 1949)
Keywords: Commerce -- Mzab

Le commerce mozabite et son influence sur la vie familiale - Chiron (Les Pères blancs: revue mensuelle des missionnaires d'Afrique, 1953)
Keywords: Commerce -- Mzab